(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In the present paper we analyze the mestizaje and inter-ethnic relations that arose throughout colonial New Spain, through marriages that took place in the city of Guanajuato in 1778. We also examine the mechanisms and criteria used by the Spanish Crown to identify and diferentiate the inhabitants of New Spain. he structure of this article can be broken down to three analytical sections: geographical-social, social (covering some of the dynamics of coexistence in this city, such as marriage) and the question of honor as a constraint to the mestizaje, at least in the groups with a high economic status.